Don't Look It Up. - Min Li Chan (New England Review (10531297), 2022)
The author explores the algorithm of language and its use as a tool for communication. She tells about attempts of artificial intelligence to make predictions of what she will say and how this made her feel that her free will had been usurped. She discusses ethics and moral thinking as caring and having responsibility towards words and expressions spoken in ordinary language. She explains language and speech as statistical systems of causality and the error propagation in computer operation.